Mussels in the Huron River Above Ann Arbor in 1969 - Henry Van der Schalie (Hello World!, 1970)
In mid December, 1969, repairs are made to the Argo damn at Ann Arbor, Michigan. Consequently, the water in the Huron River between the Barton and Argo dams was unusually low. Although the weather was bitter cold, it was an ideal location for making some observations on the mussels in an area below Barton dam where conditions allowed someone impounded, were still shoal like and where the original fauna was most likely to be retained.